2019
DOI: 10.1055/s-0039-1690243
|View full text |Cite
|
Sign up to set email alerts
|

BF3·OEt2-Catalyzed Synthesis of anti-β-(N-Arylamino)-α-hydroxynitriles by Regio- and Diastereospecific Ring Opening of 3-Aryloxirane-2-carbonitriles with Anilines

Abstract: A safe and convenient synthetic method to anti-β-(N-arylamino)-α-hydroxynitriles from 3-aryloxirane-2-carbonitriles and anilines was developed under the catalysis of BF3·OEt2 in ethanol. In this method, BF3·OEt2 first reacts with ethanol to produce the true catalyst of super­ acid H[B(OEt)F3], followed by an acid-catalyzed regio- and diastereospecific ring opening of oxirane-2-carbonitriles with anilines, generating anti-β-(N-arylamino)-α-hydroxynitriles. The method features the advantages of non-metal catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…We postulated that the deoxygenation process should involve nucleophilic opening of the expoxide ring with tetramethylthiourea. Previous work suggested that the nucleophilic attack could take place either at the cyano side to afford alkoxide A (Scheme a, mode i) or at the Ar side to generate B (Scheme a, mode ii) . Xu and co-workers reported that the BF 3 ·OEt 2 -catalyzed nucleophilic ring opening with anilines followed mode i, while our previous phosphine-catalyzed isomerization of cyanoepoxides was suggested to follow mode ii .…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…We postulated that the deoxygenation process should involve nucleophilic opening of the expoxide ring with tetramethylthiourea. Previous work suggested that the nucleophilic attack could take place either at the cyano side to afford alkoxide A (Scheme a, mode i) or at the Ar side to generate B (Scheme a, mode ii) . Xu and co-workers reported that the BF 3 ·OEt 2 -catalyzed nucleophilic ring opening with anilines followed mode i, while our previous phosphine-catalyzed isomerization of cyanoepoxides was suggested to follow mode ii .…”
Section: Resultsmentioning
confidence: 79%
“…Previous work suggested that the nucleophilic attack could take place either at the cyano side to afford alkoxide A (Scheme a, mode i) or at the Ar side to generate B (Scheme a, mode ii) . Xu and co-workers reported that the BF 3 ·OEt 2 -catalyzed nucleophilic ring opening with anilines followed mode i, while our previous phosphine-catalyzed isomerization of cyanoepoxides was suggested to follow mode ii . The reactions of cis - 1r , trans - 2r , and cis - 1s and trans - 2s clearly demonstrated the nucleophilic ring opening at the more electrophilic and sterically less hindered cyano sides via intermediates B .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Scheme 10. Diastereoselective synthesis of β-lactams.Oxiranecarbonnitriles are very important synthetic intermediates and have been applied in several transformations[46][47][48][49][50]. During the transformation of 3-substituted transoxiranecarbonnitriles 58 to 3-substituted (Z)-propenonitriles 60 through the thiourea-mediated stereospecific deoxygenation, trans-oxiranecarbonnitriles 58 generated (Z)-Scheme 10.…”
mentioning
confidence: 99%
“…However, the stability of the π-stacking interaction decreased along with the increase in the reaction temperature, resulting in the intermediate E converting into intermediate F, which generated trans-βlactam product 53 (Scheme 10)[44]. The intramolecular π-stacking interaction played an important role in controlling the formation of cis-β-lactam product 54 diastereoselectively at low temperatures.Oxiranecarbonnitriles are very important synthetic intermediates and have been applied in several transformations[46][47][48][49][50]. During the transformation of 3-substituted transoxiranecarbonnitriles 58 to 3-substituted (Z)-propenonitriles 60 through the thiourea-mediated stereospecific deoxygenation, trans-oxiranecarbonnitriles 58 generated (Z)-propenonitriles…”
mentioning
confidence: 99%